UNM MOBILE: A Campus Profile and Information Application of Universitas Negeri Makassar - Nurhidayatullah, Muhammad; Nabilah, Ersya; Paradifa, Tania; Lestary, Fitriyanty Dwi (PT. Lontara Digitech Indonesia, 2025)
UNM Mobile is an Android-based application that provides integrated access to the official profile and information of Universitas Negeri Makassar (UNM). It was developed to simplify information access for the academic community and the public. This study aims to design the application as an effective and user-friendly campus information platform using the agile development method. Key features include the university profile, news, academic calendar, class schedules, and other digital services. Testing results show that the application meets user needs in terms of accessibility and information completeness. UNM Mobile supports the digitalization and efficiency of information dissemination within UNM.